Cr(VI) removal from aqueous solution using activated carbon prepared from Ziziphus spina–christi leaf. (11th January 2019) - Abshirini, Yousef; Foroutan, Rauf; Esmaeili, Hossein
Abstract: In this study, a biosorbent prepared from Ziziphus spina-christi leaf was used in order to remove Cr(VI) from aqueous solution. To do this, Ziziphus spina-christi leaf firstly was heated for 3 h at 600 °C until it converted into charcoal powder. Afterward, its surface characteristics were evaluated using different analysis such as BET, SEM, FTIR, TEM, XRD, EDAX and MAP. Then, the effect of various parameters including pH, adsorbent dosage, contact time, temperature and initial ion concentration was examined on the Cr(VI) ion removal from aqueous solution and the optimum operating conditions to reach the maximum adsorption efficiency was obtained. The results showed that an optimum adsorption efficiency of 97.22% was obtained at a temperature of 60 °C, pH = 2, contact time of 55 min, the initial concentration of 10 mg l −1 and adsorbent dosage of 5 g l −1 . Also, the adsorption process was fully studied in terms of equilibrium, kinetic and thermodynamic factors and it showed that the adsorption process followed the Langmuir and pseudo-second order kinetic models. In addition, the maximum adsorption capacity of Cr(VI) using Langmuir isotherm was 13.81 mg g −1 . Moreover, the results of the thermodynamics studies revealed that the removal of chromium ion by coaly Ziziphus spina-christi leaf powder is an endothermic process.